PENERAPAN METODE ROLE PLAYING DALAM MENINGKATKAN HASIL BELAJAR BAHASA INDONESIA SISWA KELAS IV SDN 12 SINDUE - Solihin, Iramadhana (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2023)
This study aims to improve the results of learning Indonesian using the role playing method for fourth grade students at SDN 12 Sindue, Donggala Regency. In the Indonesian subject, grade IV students have not been able to achieve the KKM that has been determined by the teacher. This type of research is classroom action research in collaboration with class IV teachers at SDN 12 Sindue. The subjects in this study were teachers and fourth grade students at SDN 12 Sindue, totaling 23 students. The data collection technique in this study was through evaluation tests and observations during the learning process. Data analysis in this study used descriptive qualitative and quantitative observation sheets to describe the results of the scores obtained by students. The results of the study show that learning Indonesian by applying role playing learning can improve the learning outcomes of fourth grade students at SDN 12 Sindue, Donggala Regency. An increase in student learning outcomes occurred after carrying out the role playing method, namely students playing roles with their group mates on message material over the phone to understand Indonesian language lessons. Indonesian language learning outcomes increased from cycle 1 to cycle 2. The percentage of completeness of student learning outcomes increased from 69.57% to 82.61%. Students who don't participate in groups are approached by the teacher and directed to ask their friends so that all students can understand the material and can play their roles well. It can be concluded that the use of the role playing method can improve the learning outcomes of Indonesian in grade IV elementary school students.